Economic risks of development of the Southern macroregion in the context of foreign economic sanctions - Mitrofanova , Inna V.; Kalinina , Alla E.; Ivanova , Tatiana B. (Economy of Regions, 2025)
Тraditional risk management in stock markets distinguishes between systematic and idiosyn-cratic risks, whereas regional economic risk is often assessed in aggregate. This study aims to analyse re-gional economic risk by distinguishing between systematic and idiosyncratic components to evaluate their impact on the stability of development in a constituent entity of the Russian Federation. The study em-ploys statistical analysis using a modified CAPM model adapted for regional economies and content anal-ysis of regulatory legal acts related to socio-economic transformation. The latter is conducted through a keyword registry based on industry classifications included in sanctions packages. The key contribution of this study lies in the development and validation of a methodology for calculating regional systematic and idiosyncratic risks, which serves as a basis for refining strategic development priorities for Russian regions. Systematic risk arises from macroeconomic factors beyond the control of individual regions, with sanc-tions exerting similar economy- wide effects. Idiosyncratic risk, by contrast, stems from sanctions targeting specific legal entities and individuals. Rostov and Volgograd Oblasts exhibit the highest dependence on nationwide economic conditions, while Sevastopol, the Republic of Kalmykia, and Astrakhan Oblast show lower systematic risk but higher idiosyncratic risk due to regional economic structures. Content analysis indicates shifts in the risk profile of the Southern Federal Okrug in response to imposed sanctions. From a policy perspective, regions with higher systematic risk require greater federal support. The findings help evaluate differences in systematic risk across regions and guide strategies to mitigate its impact through federal budget allocations. Future research could focus on identifying the main factors influencing idio-syncratic risk and creating a unified framework for risk assessment, from individual financial portfolios to the broader macroeconomic level.